Democracy in Nepal: The Status of Inclusive Representation - Lamsal, Rajan; Thapa, Asim; Koirala, Narayan (Innovative Research Journal, 2023)
One of the fundamental tenets of liberal democracy is political representation. In Nepal, ethnopolitics has emerged as one of the most important political debates and issues. The primary causes of the current political environment are the effects of globalization and numerous political upheavals. In the Asian environment in general and Nepal in particular, inclusive democracy is a key contentious political principle. The political and non-political concerns that pertain to inclusive democracy are the main subject of this article. According to the text and a broader perspective, inclusiveness can fight social exclusion.